2016
DOI: 10.1016/j.jvs.2016.02.049
|View full text |Cite
|
Sign up to set email alerts
|

Predicting loss of patency after forearm loop arteriovenous graft

Abstract: Radial artery selection as inflow artery was independently associated with primary patency after AVG.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 18 publications
1
5
0
Order By: Relevance
“…Sensitivity analysis of the patency rates after primary and secondary operations, and at the end of the study, corroborated the superiority of pRBAVF; the primary patency rate was ≥5% higher that of BBVAF, while the secondary and overall patency rates were similar between the methods. These results are in line with the results of the study by Suemitsu et al [28] that indicates the selection of the radial artery contributes to the higher primary patency rate. Rosas et al [29] reported that AVF was useful when the maturation rate was ≥69%, and evaluated the costeffectiveness of initial AVF and synthetic vascular access in hemodialysis patients.…”
Section: Discussionsupporting
confidence: 92%
“…Sensitivity analysis of the patency rates after primary and secondary operations, and at the end of the study, corroborated the superiority of pRBAVF; the primary patency rate was ≥5% higher that of BBVAF, while the secondary and overall patency rates were similar between the methods. These results are in line with the results of the study by Suemitsu et al [28] that indicates the selection of the radial artery contributes to the higher primary patency rate. Rosas et al [29] reported that AVF was useful when the maturation rate was ≥69%, and evaluated the costeffectiveness of initial AVF and synthetic vascular access in hemodialysis patients.…”
Section: Discussionsupporting
confidence: 92%
“…To our knowledge, there is no existing meta-analysis regarding AVG patency rates. One recent study 6 from a multicenter cohort in Japan showed a one-year primary patency rate of 25% and a one-year secondary patency rate of 85%. Our cohort showed slightly better primary patency outcomes and similar secondary patency outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…The primary patency rate was significantly different between the radial artery and brachial artery inflow at one year (53.8% versus 24.4%, P=0.032). 10) Our study showed a different result: in all cases, the inflow artery chosen in our study was the brachial artery with a size larger than 2 mm. Moreover, the primary patency was 58.82% at one year.…”
Section: Discussionmentioning
confidence: 72%